Selection and Scheduling of Actions for Innovation Capabilities Improvement - Vasquez-Perez, O; Rojo-Gonzalez, L (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper introduces the selection and scheduling problem of actions for improving the innovation capability (IC) of an enterprise based on expert assessment using a particular maturity grids for its measurement, in which budget and time limit constraints are imposed. To address this problem, we study its computational complexity and formulate a binary integer linear programming (BILP) for an exact resolution, which meets IC targets and minimizes the total cost of the schedule for the selected actions. To illustrate the usefulness of the proposed model, a numerical example based on a French textile company is considered. © 2019 IEEE.
Keywords: Selection; Scheduling; Innovation capability